Avaliação do desenvolvimento de Mentha crispa L. em solo contaminado com cádmio - Zemiani, Adriana (2017)
The objective of this work was to evaluate the behavior of Mentha crispa L. (Garden Mint) in a soil contaminated with different concentrations of Cd. The experimental design was done with five replicates distributed in eight treatments (C0 (control), C1 (1.15 g.kg-1), C2 (1.53 g.kg-1), C3 (2.30 g.kg-1), C4 (4,60 g.kg-1), C5 (9.21 g.kg-1), C6 (18.25 g.kg-1) and C7 (36.87 g.kg-1)). The C5 treatment used the maximum concentration of metal absorbed by the soil, determined through the adsorption isotherm using the Langmuir equation model. The plants were cultivated for 120 days, from June to August 2016, and every 15 days data were collected such as height, number of leaves and number of shoots. Records were made to evaluate the visual symptomatology observing the behavior of the plant in each treatment throughout the experiment period. At the end of the treatment the plants were collected and separated into three parts (leaves, stem and root) and submitted to microwave assisted acid digestion to determine cadmium through Atomic Absorption Spectrometry. It was observed that the height, number of shoots and number of leaves decreased as the concentrations of Cd increased in the treatments. Symptoms of Cd toxicity were observed in plants, such as: chlorosis, leaf blight and wilting. Plants fromC6 and C7 treatments died within 48 hours after contact with contaminated soil. Considering the total amount of cadmium absorbed by the plant, most were retained by the roots and an insignificant part was translocated to the aerial part (stem and leaves). The bioaccumulation factors were calculetd in all treatments and they was greater than one, indicating that the plant is able to accumulate Cd. The plant translocation factor was lower than one in all treatments demonstrating that although a Mentha crispa L. accumulates Cd, it can not be classified as hyperaccumulating, but as phytoextabilizing. Therefore, the Mentha crispa L. can be used to immobilize the metal in contaminated sites. The fact that the metal has pratically not been translocated to the aerial part can be a favorable point in the choice of the plant to be used in the phytoremediation, since the Mentha crispa L., from the economic point of view, may have added value in the extraction of the essential oil, which is produced by the leaves.